EFFECTIVENESS OF DAYAK BULUSU DANCE INTERACTIVE MEDIA ON PANCASILA STUDENT PROFILE CHARACTER IN ELEMENTARY SCHOOL STUDENTS - Chintyawaty; Shirly Rizki Kusumaningrum; Slamet Arifin; Ibrahim Bafadal; Radeni Sukma Indra Dewi (RADJA PUBLIKA, 2025)
This study aims to investigate the impact of using interactive teaching materials based on the Dayak Bulusu traditional dance on strengthening the Pancasila Student Profile character in elementary school students. The research employed a quasi-experimental method with a nonequivalent control group design. The participants were fifth-grade students from a public elementary school in North Kalimantan, selected through purposive sampling. Data were collected using a character assessment instrument that referred to the six dimensions of the Pancasila Student Profile and were analyzed using an independent sample t-test. The findings reveal a significant improvement in students’ character, particularly in the aspects of mutual cooperation, independent learning, and cultural diversity appreciation, in the experimental group using the interactive teaching materials. These results suggest that integrating local cultural content into interactive learning resources effectively promotes character education aligned with the Pancasila Student Profile. The study recommends that interactive materials rooted in indigenous culture be continuously developed as innovative media in elementary education, especially within the framework of the Merdeka Curriculum.